Aborto, derecho e ideología - Claudia Escobar García (Universidad Hemisferios, 2008)
This work explains that the discourses opposing the criminalization ofabortion and that reject the constitutional rules that protect human life,are an artificially constructed ideology made only to justify abortion,and hide the asymmetrical relations of power between women and theunborn. In order for this purpose, these arguments are identified andsubjected to critical analysis, demonstrating that it is purely emotionaland lacking fundaments.